Leiomiosarcoma Gástrico. A propósito de 7 casos - González, Daniel; Vicente, Juan; Ant´unez, Carlos; Tellechea, Miguel; Ayala, Daniel; Torres, Marcos; di Leoni, Francisco (Cirugía del Uruguay, 2004)
Gastric leiomyosarcoma is a rare tumor. lts clinical symptoms are non specific; its diagnosis during preoperative is genera/y difficult. Surgery is the main therapeutic pillar because neither radiation nor chemical therapy have pro ven to be effective.